PENGEMBANGAN DAN IMPLEMENTASI APLIKASI ANTRIAN LOKET PELAYANAN MASYARAKAT MENGGUNAKAN METODE MULTI CHANEL-SINGLE PHASE (Studi Kasus : Disdukcapil Kabupaten Kubu Raya) - Muhammad Sony Maulana (Jurnal Khatulistiwa Informatika, 2016)
Web-based application is an easy solution to execute a client-server concept. The web application can run on all operating systems such as Windows, Linux and Mac OS. The web application can be accessed using a browser and does not require a high specification computer. Application queue is an application that can help process the queue to display the sequence of queues based on the customers who come awal.Aplikasi queues can help a government or private agency to avoid Push-pressed between the customer when queuing to get service. Application queues are equipped with sound, pictures and text can improve the quality of public services. Keywords: queuing applications, client-server based applications